Commit a8e67a81 authored by Michael Hanus 's avatar Michael Hanus

Array removed

parent 3a437f95
--- Implementation of Arrays with Braun Trees. Conceptually, Braun trees
--- are always infinite. Consequently, there is no test on emptiness.
---
--- @authors {bbr, fhu}@informatik.uni-kiel.de
--- @category algorithm
module Array
(Array,
emptyErrorArray, emptyDefaultArray,
listToDefaultArray,listToErrorArray,
(//), update, applyAt,
(!),
combine, combineSimilar)
where
import Integer
infixl 9 !, //
data Array b = Array (Int -> b) (Entry b)
data Entry b = Entry b (Entry b) (Entry b) | Empty
--- Creates an empty array which generates errors for non-initialized
--- indexes.
emptyErrorArray :: Array b
emptyErrorArray = emptyDefaultArray errorArray
errorArray :: Int -> _
errorArray idx = error ("Array index "++show idx++" not initialized")
--- Creates an empty array, call given function for non-initialized
--- indexes.
--- @param default - function to call for each non-initialized index
emptyDefaultArray :: (Int -> b) -> Array b
emptyDefaultArray dflt = Array dflt Empty
--- Inserts a list of entries into an array.
--- @param array - array to modify
--- @param modifications - list of new (indexes,entries)
--- If an index in the list was already initialized, the old value
--- will be overwritten. Likewise the last entry with a given index
--- will be contained in the result array.
(//) :: Array b -> [(Int,b)] -> Array b
(//) (Array dflt array) modifications =
Array dflt
(foldr (\ (n,v) a -> at (dflt n) a n (const v)) array modifications)
--- Inserts a new entry into an array.
--- @param array - array to modify
--- @param idx - index of update
--- @param val - value to update at index idx
--- Entries already initialized will be overwritten.
update :: Array b -> Int -> b -> Array b
update (Array dflt a) i v =
Array dflt (at (dflt i) a i (const v))
--- Applies a function to an element.
--- @param array - array to modify
--- @param idx - index of update
--- @param fun - function to apply on element at index idx
applyAt :: Array b -> Int -> (b->b) -> Array b
applyAt (Array dflt a) n f = Array dflt (at (dflt n) a n f)
at :: b -> Entry b -> Int -> (b -> b) -> Entry b
at dflt Empty n f
| n==0 = Entry (f dflt) Empty Empty
| odd n = Entry dflt (at dflt Empty (n `div` 2) f) Empty
| otherwise = Entry dflt Empty (at dflt Empty (n `div` 2 - 1) f)
at dflt (Entry v al ar) n f
| n==0 = Entry (f v) al ar
| odd n = Entry v (at dflt al (n `div` 2) f) ar
| otherwise = Entry v al (at dflt ar (n `div` 2 - 1) f)
--- Yields the value at a given position.
--- @param a - array to look up in
--- @param n - index, where to look
(!) :: Array b -> Int -> b
(Array dflt array) ! i = from (dflt i) array i
from :: a -> Entry a -> Int -> a
from dflt Empty _ = dflt
from dflt (Entry v al ar) n
| n==0 = v
| odd n = from dflt al (n `div` 2)
| otherwise = from dflt ar (n `div` 2 - 1)
split :: [a] -> ([a],[a])
split [] = ([],[])
split [x] = ([x],[])
split (x:y:xys) = let (xs,ys) = split xys in
(x:xs,y:ys)
--- Creates a default array from a list of entries.
--- @param def - default funtion for non-initialized indexes
--- @param xs - list of entries
listToDefaultArray :: (Int -> b) -> [b] -> Array b
listToDefaultArray def = Array def . listToArray
--- Creates an error array from a list of entries.
--- @param xs - list of entries
listToErrorArray :: [b] -> Array b
listToErrorArray = listToDefaultArray errorArray
listToArray :: [b] -> Entry b
listToArray [] = Empty
listToArray (x:xs) = let (ys,zs) = split xs in
Entry x (listToArray ys)
(listToArray zs)
--- combine two arbitrary arrays
combine :: (a -> b -> c) -> Array a -> Array b -> Array c
combine f (Array def1 a1) (Array def2 a2) =
Array (\i -> f (def1 i) (def2 i)) (comb f def1 def2 a1 a2 0 1)
comb :: (a -> b -> c) -> (Int -> a) -> (Int -> b)
-> Entry a -> Entry b -> Int -> Int -> Entry c
comb _ _ _ Empty Empty _ _ = Empty
comb f def1 def2 (Entry x xl xr) Empty b o =
Entry (f x (def2 (b+o-1)))
(comb f def1 def2 xl Empty (2*b) o)
(comb f def1 def2 xr Empty (2*b) (o+b))
comb f def1 def2 Empty (Entry y yl yr) b o =
Entry (f (def1 (b+o-1)) y)
(comb f def1 def2 Empty yl (2*b) o)
(comb f def1 def2 Empty yr (2*b) (o+b))
comb f def1 def2 (Entry x xl xr) (Entry y yl yr) b o =
Entry (f x y)
(comb f def1 def2 xl yl (2*b) o)
(comb f def1 def2 xr yr (2*b) (o+b))
--- the combination of two arrays with identical default function
--- and a combinator which is neutral in the default
--- can be implemented much more efficient
combineSimilar :: (a -> a -> a) -> Array a -> Array a -> Array a
combineSimilar f (Array def a1) (Array _ a2) = Array def (combSim f a1 a2)
combSim :: (a -> a -> a) -> Entry a -> Entry a -> Entry a
combSim _ Empty a2 = a2
combSim _ (Entry x y z) Empty = Entry x y z
combSim f (Entry x xl xr) (Entry y yl yr) =
Entry (f x y) (combSim f xl yl) (combSim f xr yr)
Markdown is supported
0% or
You are about to add 0 people to the discussion. Proceed with caution.
Finish editing this message first!
Please register or to comment